Development of tourist guide interactive map of Cameron Highland using GIS-based spatial decision support system / Shedatul Rabia Aishah Abdul Rahman - Abdul Rahman, Shedatul Rabia Aishah (2019)
Cameron Highlands is one of the tourism areas, also one of the best attraction places in Malaysia that the tourist came from the inside and outside of the country. To promote well the best destination in the Cameron Highlands, one web is built in this study to guide the tourist by using the web and interactive map and, also by adding the Spatial Decision Support System to give the best decision making to the user. GIS functions are simply not appropriate to facilitate the planning of garden visitor activities. This paper presents a web-based GIS-based spatial decision support system that integrates GIS functionality and SDSS design with a simple graphical user interface to help Cameron Highlands visitors choose and plan their activities more effectively to customize their personal preferences and constraints. The design for this web-based is a user-friendly interface, which guides the users through the web in an intuitive and informative manner and the important part is a consideration during the applications development. The user interface should be the user's needs when visiting Cameron Highlands.